2015
DOI: 10.1017/s0022215114003223
|View full text |Cite
|
Sign up to set email alerts
|

Case report of a p16INK4A-positive branchial cleft cyst

Abstract: Histological and immunohistochemical analyses support the cystic transformation of lymph nodes, or the 'Inclusion Theory', as the aetiology of branchial apparatus anomalies, and raise the possibility that human papillomavirus infection may play a much larger role in disease of the head and neck than previously supposed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…Soh suggested that most cases of branchiogenic carcinomas reported in the literature may have been secondary metastatic lesions from an occult tonsillar carcinoma [ 11 ]. A case report by McLean presented a patient with concurrent oropharyngeal squamous cell carcinoma and branchial cleft cyst that were positive for P16 and HPV DNA [ 35 ]. Lack of evidence of carcinogenic change of the normal epithelium and an identifiable normal lymphoepithelial lining of a cystic space would fail to prove that the tumor originated from the epithelium, and fail to differentiate it from a central necrotic metastatic lymph node [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…Soh suggested that most cases of branchiogenic carcinomas reported in the literature may have been secondary metastatic lesions from an occult tonsillar carcinoma [ 11 ]. A case report by McLean presented a patient with concurrent oropharyngeal squamous cell carcinoma and branchial cleft cyst that were positive for P16 and HPV DNA [ 35 ]. Lack of evidence of carcinogenic change of the normal epithelium and an identifiable normal lymphoepithelial lining of a cystic space would fail to prove that the tumor originated from the epithelium, and fail to differentiate it from a central necrotic metastatic lymph node [ 7 ].…”
Section: Discussionmentioning
confidence: 99%